Non-surgical endodontic treatment of maxillary first molar with large size and curved canal: a case report - Habib, Adnan; Doumani, Mazen; Almutairi, Muteb (International Journal of Dental Research, 2018)
The teeth are subjected to considerable variation for the number, size, form and structure of dental tissues. In this rare case report, a 30-year-old male patient was referred for root canal treatment of his right maxillary first molar because of deep caries in this tooth. During radiographic examination for determining the working length of this tooth, the peri-apical radiographs revealed the unfamiliar size of the maxillary first molar, in addition to severe curvature in mesiobuccal root. To achieve a successful treatment instrumentation of the canals completed with a crown-down technique, and obturation was done with lateral condensation technique.